Respuesta :

Answer:

X=5

y=3

Step-by-step explanation:

you’re welcome

Answer:

  • x = 5
  • y = 3

Solution:

  • => x + 4y = 17

            -x - 6y = -23

  • => -2y = -6
  • => y = 3

Now, let's substitute the value of y into the first equation.

  • x + 4y = 17
  • => x + 4(3) = 17
  • => x + 12 = 17
  • => x = 5

Let's check our answer to make sure it is correct.

Check:

  • -x - 6y = -23
  • => -(5) - 6(3) = -23
  • => -5 - 18 = -23
  • => -23 = -23

Hence, this is proven correct.

Hoped this helped.

[tex]BrainiacUser1357[/tex]